Effective Meetings - Lisa A. Guion; Elizabeth B. Bolton (EDIS)
This lesson contains practical information on planning and conducting effective meetings. Topics covered include preparing for the meeting, getting the meeting off to a good start, creating an atmosphere for participation, moving the meeting forward to get results, ending the meeting, and following up after the meeting. Each topic highlights how to maximize meeting productivity and effectiveness. This document is PE051, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Publication date: August 2003.